INISIASI RONGGENG DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI KAJIAN RESPON ESTETIK - Inung Setyami (sarasvati, 2021)
This study aims to describe the world of ronggeng in Ahmad Tohari's novel Ronggeng Dukuh Paruk in terms of Wolfgang Iser's Aesthetic Response theory. The source of research data is the novel Ronggeng Dukuh Paruk by Ahmad Tohari published in 2011 by PT. Gramedia Pustaka Utama. The data collection technique was done by reading notes, namely reading accompanied by careful and thorough recording of the whole novel related to the ronggeng repertoire. This research is a qualitative descriptive study. This technique is carried out through the steps 1) reading, 2) identification, 3) classification, 4) interpretation, and 5) inference. The results showed that 1) Through reading based on Iser's repertoire theory, the culture revealed in the Ronggeng Dukuh Paruk novel can be seen. The culture that was revealed was the culture of the Javanese people, especially the existence of the traditional ronggeng art; 2) Peronggengan in Java, traditionally cannot be separated from the initiation of "peronggengan" as a prerequisite for someone to become ronggeng; and 3) There is a pergowokan profession whose existence intersects with the world of ronggeng.  Keywords: repertoire, wolfgang iser, ronggeng dukuh paruk, gowok